Evaluation of carotid intima-media thickness in children with migraine: a marker of subclinical atherosclerosis - Poyrazoglu, Hatice Gamze; Vurdem, Umit Erkan; Arslan, Alev; Uytun, Salih (Springer-Verlag Italia Srl, 2016)
Migraine is a commonly seen neurovascular disorder during childhood. Inflammation induced by the activation of cytokines and neuropeptides is implied in its pathophysiology. There is an association between inflammation and atherosclerosis in patients with migraine. In addition, there is a strong correlation between early atherosclerotic wall lesions and carotid intima-media thickness (CIMT). The study population consisted of 57 migraine patients aged 5-17 years, as well as 47 healthy children who served as the control group. Those migraine patients who were not receiving any medications at the interictal period were compared to healthy controls in terms of their measured lipid levels, thyroid function, vitamin B12 levels, serum iron levels, iron binding capacity, complete blood count, C-reactive protein (CRP) levels, and carotid intima-media thickness (CIMT) scores, which may comprise risk factors for atherosclerosis. When children in the migraine and control groups were compared in terms of those risk factors that are known to be related to vascular changes, no significant differences were found. However, a significant difference was detected in CIMT values (P < 0.05). Atherosclerosis commences in childhood, and there is a long period of time before the onset of ischemic symptoms occurs. In children with migraine, an evaluation of CIMT can be used as a non-invasive imaging modality to detect atherosclerosis, which develops in the context of chronic inflammation. In this way, measures to reduce morbidity and mortality, which may result from cardiovascular diseases, can be implemented.
Keywords: Migraine; Subclinical atherosclerosis; Carotid intima-media thickness; Child